Performance of hemodynamic stability parameters as predictors of ectopic pregnancy, with emphasis on shock index - Khan, Bijay; Chakraborty, Mayoukh Kumar; Basu, Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: A study was conducted to determine the utility of shock index in the diagnosis of acute rupture ectopic pregnancy (EP). Methods: A retrospective review of all ruptured ectopic pregnancy at KPC medical college and hospital a tertiary private health care centre was performed for two years (May 2018 to April 2020). During this study, we used data of 35 cases of EP among 1150 pregnant ladies admitted from time to time under emergency. Results: The mean age of the study population was 29.49±0.74 (mean±SEM) years (range 22-38 years) and mean gestational period of pregnancy was 42.2±2.0 days (range 28-90 days). The commonest presentation of clinical symptoms associated with EC was abdominal pain (91%), vaginal bleeding (89%), amenorrhea (86%), dizziness/fainting attack (17%) and shock (68%). In majority (92.3%) of the patients the shock index was >0.70 with an average of 0.9±0.03. In 60.7% of the cases the amount of haemoperitoneum found at laparatomy was >1000 ml. It was observed that most patients with EP had hemoperitoneum above 1000 ml (1140±113.6). Conclusions: Pulse rate or systolic blood pressure alone are not a good predictor to access the amount of blood loss in EP. But when they were used to calculate the SI (shock index), it was more accurate and simpler predictor for diagnosis of EP. SI may be used in guiding clinicians in providing appropriate management for EP patients especially in low-resource settings or hospitals with limited facilities.